2011
DOI: 10.1063/1.3554686
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced optoelectronic performance from the Ti-doped ZnO nanowires

Abstract: Ti-doped ZnO nanowires (NWs) were fabricated by thermal evaporation and metal vapor vacuum arc (MEVVA) ion implantation process. The effect of Ti doping on the structure, morphology, and electrical/optical properties of the as-grown NWs was investigated. The fraction of Ti doping was estimated to be 1 at. % to 2 at. % based on energy-dispersive x-ray spectroscopy (EDS). The x-ray diffraction analyses indicated that Ti-doped ZnO NWs are similar to ZnO NWs in crystal structure, which has been taken to indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 40 publications
2
19
1
Order By: Relevance
“…The UV blueshift was also detected in the cathodoluminescence (CL) spectra of ZnO NWs irradiated with 30-keV Ti + ions. Nevertheless, in this case, the visible emission did not suffered changes with the implantation doses [29], contrary to the behavior observed by Wang et al [30] who reported a complete disappearance of the visible emission from ZnO NWs irradiated with 2-keV H + ions. Hence, the modification of the luminescence properties of ZnO after irradiation experiments is still not clearly understood and, even less, after low energy irradiation experiments.…”
Section: Introductioncontrasting
confidence: 71%
“…The UV blueshift was also detected in the cathodoluminescence (CL) spectra of ZnO NWs irradiated with 30-keV Ti + ions. Nevertheless, in this case, the visible emission did not suffered changes with the implantation doses [29], contrary to the behavior observed by Wang et al [30] who reported a complete disappearance of the visible emission from ZnO NWs irradiated with 2-keV H + ions. Hence, the modification of the luminescence properties of ZnO after irradiation experiments is still not clearly understood and, even less, after low energy irradiation experiments.…”
Section: Introductioncontrasting
confidence: 71%
“…Thus, the optimum behaviour of Ti as an electrical dopant takes place for 10 concentrations below 1 at.%. A similar behaviour, but with a Ti load threshold of 1.3 at.%, has been reported for 500nm 16 43 . According to the above exposed, ZnO samples doped with a 0.5at.% of Ti and thicknesses down to 10nm may be suitable for electronic and optoelectronic devices, 25 solar cells, photoelectrodes, photocatalysts or sensors.…”
supporting
confidence: 50%
“…Next, the surface roughness (due to the presence of surface defects) and impurity may cause electron scattering, leading to the limited mobility. It is still higher than other application of photodetector of oxide semiconductor materials [33-35]. This implies that it may affect the sensitivity of the photodetector.…”
Section: Resultsmentioning
confidence: 95%